Flavor differences of soybean and defatted soybean fermented soy sauce and its correlation with the enzyme profiles of the kojis. (25th August 2022) - Tian, Yi‐Fan; Chen, Yu‐Xing; Tong, Xing; Hou, Sha; Zhao, Mou‐Ming; Feng, Yun‐Zi
Abstract: BACKGROUND: Soybeans and defatted soybeans, commonly used as protein ingredients, have different flavors of their fermented soy sauce. Clarifying the differences between the two soy sauces, as well as the formation mechanism, is an important prerequisite for improving the flavor of defatted soybean soy sauce. To this goal, the aroma characteristics of two soy sauces and their volatile profiles were compared by sensory evaluation and gas chromatography‐mass spectrometry, and eight enzyme activities and volatile profiles of matured koji were determined. RESULTS: Sensory results showed that the acids, fruity and cooked potato‐like attributes were higher in whole soybean fermented soy sauce, whereas defatted soybean soy sauce exhibited higher smoky and malty attributes, closely related to the contents of aroma‐active compounds in soy sauce, such as isobutyl acetate, 2/3‐methylbutanal, acetic acid and 2/3‐methylbutanoic acid. The content of most volatiles in the matured koji s showed a consistent trend with that of soy sauce: alcohols, acids, furan(one)s and ketones. Interestingly, acid protease and cellulase activities were 3.3 and 1.6 times higher in the whole soybean koji than in defatted soybean koji, respectively, whereas neutral protease, aminopeptidase, glucoamylase and β ‐glucosidase were approximately 2.0 times higher in defatted soybean koji . CONCLUSION: In summary, the flavor differences between soybean and defatted soybean fermented soy sauce were not only caused by the differences in the content of flavor precursors in the materials, but also closely related to the differences in the enzymatic profiles accumulated during the koji ‐making process. © 2022 Society of Chemical Industry.